Aliansi Etnis Kurdi di Perbatasan Selama Krisis Politik Suriah Tahun 2011-2016 - Hapsari, Renitha Dwi (Global and Policy Journal of International Relations, 2019)
Ethnic Kurds live in the border area of several countries. They formed ethnic alliances based on ethnic kin. In 2011, when the political crisis occurred in Syria, Syrian Kurds became one of the opposition group, which opposed the government. John W. Crow and R. Noel stated that authoritarian governments generally respond to insecurity by implementing aggressive or militaristic approach. In this case, the Syrian Government uses violence and militaristic actions to suppress the power of opposition groups. Based on Tikhomirov, the response could increase the tendency for separatist groups - territorial and ethnic nationalism. The political crisis also weakens the power and capability of the government, along with the increasing pressure from opposition groups and mass mobilization. This is an opportunity for the Kurdish secessionist movement in Syria. As Peter Ferdinand stated that when strife increases and causes insecurity within the country, the nationalism that can survive is ethnic nationalism. The author also used Suhrke and Noble who stated that the support provided by blood brothers has a significant impact on ethnic groups who facing conflict, both with the state or other ethnic groups. Keywords: Ethnic alliances, political crisis, secessionist movement DOI : https://doi.org/10.33005/jgp.v7i01.1810